Evolution of approaches to the treatment of atrial fibrillation: a comparative analysis of ABC (2020) and AF-CARE (2024) - Detyukova, K. D. (Запорізький державний медико-фармацевтичний університет, 2025)
Aim: To compare the new AF-CARE approach with the previous ABC.
Keywords: тези доповідей